Improving accuracy of altimeter-derived marine gravity anomalies in the East Vietnam Sea deep-basin and adjacent area - Dung, Tran Tuan; Sang, Nguyen Van; Dai, Nguyen Ba; Dung, Nguyen Kim; Lap, Tran Trong; Duong, Tran Tuan; Ha, Nguyen Thi Hai (Vietnam Journal of Marine Science and Technology, 2019)
In recent years, the satellite altimeter technology allows enhancing the marine investigation in many areas. Up to now, many scientific studies have attempted to improve the accuracy and resolution of altimeter-derived gravity anomalies and have produced a gravity grid with interval of 1’×1’ for most oceans all over the world. However, these gravity anomalies are not very highly accurate and have a large difference compared to shipboard gravity anomalies, especially in the coastal and islands areas. The purpose of this article is to improve the accuracy of altimeter-derived marine gravity anomalies for geological structure research in the East Vietnam Sea deep-basin and adjacent areas. The least squares collocation method is used to correct the altimeter-derived marine gravity data based on the shipboard gravity data in order to improve the accuracy of marine gravity anomalies. In this article, the altimeter-derived marine gravity anomalies are taken from Sandwell, D. T., et al., (V24.1) and the shipboard gravity anomalies are from the survey projects between Vietnam, Russia and other countries. The mean-squared error when comparing both data is about 9,358 mGal. After correcting by collocation method, the error was reduced to 3,208 mGal (for the altimeter data coinciding with shipboard track). Also, in this article, the achieved results show the efficiency and actuality of the corrected-altimeter-derived marine gravity anomalies for more detailed researches of geological structures. Especially, it is more meaningful in the remote or sparsely surveyed regions.